Y2SK2 and SK3 type dehydrins from Agapanthus praecox can improve plant stress tolerance and act as multifunctional protectants. (July 2019) - Yang, Zhou; Sheng, Jiangyuan; Lv, Ke; Ren, Li; Zhang, Di
Highlights: The ApY2SK2 and ApSK3 dehydrin genes from Agapanthus praecox can enhance stress tolerance of transgenic plant. ApY2SK2 and ApSK3 protein can act as multifunctional in vitro protectants and improve cell viability under complex stresses. ApY2SK2 showed better enzyme protection function and ApSK3 had stronger metal ion binding function. Abstract: Two dehydrins from Agapanthus praecox ( ApY2 SK2 and ApSK3 ) show important protective effects under complex stresses. Both ApY2 SK2 and ApSK3 contain one intron and consist of a full-length cDNA of 981 bp and 1057 bp encoding 186 and 215 amino acids, respectively. ApY2 SK2 and ApSK3 transgenic Arabidopsis thaliana show reduced plasma membrane damage and ROS levels and higher antioxidant activity and photosynthesis capability under salt, osmotic, cold and drought stresses compared with the wild-type. ApY2 SK2 and ApSK3 are mainly located in the cytoplasm and cell membrane, and ApY2 SK2 can even localize in the nucleus. In vitro tests indicate that ApY2 SK2 and ApSK3 can effectively protect enzyme activity during the freeze-thaw process, and ApY2 SK2 also exhibits this function during desiccation treatment. Furthermore, ApY2 SK2 and ApSK3 can significantly inhibit hydroxyl radical generation. These two dehydrins can bind metal ions with a binding affinity of Co 2+ > Ni 2+ > Cu 2+ > Fe 3+ ; the binding affinity of ApSK3 is higher than that of ApY2 SK2 . Thus, ApY2 SK2 has a better protective effect on enzyme activity, and ApSK3 has stronger metal ion binding function and effect on ROS metabolism. Moreover, plant cryopreservation evaluation tests indicate that ApY2 SK2 and ApSK3 transformation can enhance the seedling survival ratio from 23% to 47% and 55%, respectively; the addition of recombinant ApY2 SK2 and ApSK3 to plant vitrification solution may increase the survival ratio of wild-type A. thaliana seedlings from 24% to 50% and 46%, respectively. These findings suggest that ApY2 SK2 and ApSK3 can effectively improve cell stress tolerance and have great potential for in vivo or in vitro applications.